Concurrent creatine monohydrate supplementation and resistance training does not affect markers of hepatic function in trained weightlifters - Waldron, J. E.; Pendlay, G. W.; Kilgore, T. G.; Haff, G. G.; Reeves, J. S.; Kilgore, J. L. (Journal of Exercise Physiology online, 2002)
This study examined five days of creatine loading followed by five weeks of maintenance during weight training and its affect on hepatic enzymes that mark liver stress. Eight subjects participated in 5 weeks of high intensity Olympic-style weight-training that followed one week of enforced rest. Hepatic stress was assessed through measurement of serum concentrations of alanine amino transferase (ALT), aspartate amino transferase (AST) and alkaline phosphatase (AP). Testing occurred weekly, starting after one week of inactivity to establish baseline values and continuing for five training weeks. Blood urea nitrogen (BUN), albumin, creatinine, and direct and total bilirubin (DB and TB) concentrations were monitored as supplemental markers of hepatic stress. After loading and maintenance, concentrations of analytes did not vary. Final data indicate that the changes noted were not statistically significant and remained within normal clinical ranges.